Hoxa5 Activity Across the Lateral Somitic Frontier Regulates Development of the Mouse Sternum - Mitchel, Kira; Bergmann, Jenna M.; Brent, Ava E.; Finkelstein, Tova M.; Schindler, Kyra A.; Holzman, Miriam A.; Jeannotte, Lucie; Mansfield, Jennifer H. (Frontiers in Cell and Developmental Biology, 2022)
The skeletal system derives from multiple embryonic sources whose derivatives must develop in coordination to produce an integrated whole. In particular, interactions across the lateral somitic frontier, where derivatives of the somites and lateral plate mesoderm come into contact, are important for proper development. Many questions remain about genetic control of this coordination, and embryological information is incomplete for some structures that incorporate the frontier, including the sternum. Hox genes act in both tissues as regulators of skeletal pattern. Here, we used conditional deletion to characterize the tissue-specific contributions of Hoxa5 to skeletal patterning. We found that most aspects of the Hoxa5 skeletal phenotype are attributable to its activity in one or the other tissue, indicating largely additive roles. However, multiple roles are identified at the junction of the T1 ribs and the anterior portion of the sternum, or presternum. The embryology of the presternum has not been well described in mouse. We present a model for presternum development, and show that it arises from multiple, paired LPM-derived primordia. We show evidence that HOXA5 expression marks the embryonic precursor of a recently identified lateral presternum structure that is variably present in therians.